Advances in our understanding of immunization and vaccines for patients with systemic lupus erythematosus. (3rd October 2017) - Bragazzi, Nicola Luigi; Watad, Abdulla; Sharif, Kassem; Adawi, Mohammad; Aljadeff, Gali; Amital, Howard; Shoenfeld, Yehuda
ABSTRACT: Introduction : Systemic lupus erythematosus (SLE) is a chronic systemic autoimmune disease. In SLE, immune system dysfunction is postulated to result by virtue of the disease itself as well as by the impact of treatment modalities employed. A myriad of immune dysregulations occur including complement system dysfunction among others. Infectious agents are known to complicate the disease course in close to 25–45% of SLE patients. Areas covered : In this review a discussion of the immunogenicity and safety of viral and bacterial vaccinations in SLE was performed. The search included ISI Web of Science (WoS), Scopus, MEDLINE/PubMed, Google-Scholar, DOAJ, EbscoHOST, Scirus, Science Direct, Cochrane Library and ProQuest. Proper string made up of a key-words including 'SLE', 'vaccination', 'safety' and 'efficacy' was used. Expert commentary : Vaccination of SLE patients is proven to be immunogenic. Concerns regarding vaccine safety are postulated, yet no direct relationship between vaccination and disease exacerbation were established. While live virus vaccines are generally contraindicated in immunosuppressive states, generally live attenuated vaccinations are recommended in SLE patients on a case-to-case basis. In SLE patients, clinical parameters such as vaccination during disease exacerbations have not been intensively studied and therefore while apparently safe, vaccination is generally recommended while disease is quiescent.